simplify the expression. If not possible,write simplified.

User Generated

rnflorr41

Mathematics

Question Description

3x-3 (8-9x)

3 (9m-7)

2-2z+6-5z

3(11a+12f-2f)

Student has agreed that all tutoring, explanations, and answers provided by the tutor will be used to help in the learning process and in accordance with Studypool's honor code & terms of service.

Explanation & Answer

3x-3(8-9x) = 3x-24+27x = 3x+27x-24 =30x-24 = 3(10x-8)

3(9m-7) = 27m-21

2-2z+6-5z = 2+6-2z+5z= 8+3z

3(11a+12f-2f) = 33a+36f-6f = 33a-30f

jneerap (144)
Purdue University

Anonymous
Really helped me to better understand my coursework. Super recommended.

Studypool
4.7
Trustpilot
4.5
Sitejabber
4.4